Obtención de biodiesel a partir de aceite de fritura de los comedores de la ciudad de Requena - Del Aguila Saravia, Edinson (2025)
The present research aimed to obtain biodiesel from waste cooking oil collected from five popular canteens in the city of Requena, Loreto region. The alkaline transesterification process with methanol and potassium hydroxide (KOH) catalyst was employed. The waste oil was physically and chemically characterized obtaining average values of moisture content 0.420%, density 0.9186 g/ml, kinematic viscosity 35.672 Cp, acid value 0.8708 mg KOH/g, free fatty acids 0.4384%, peroxide value 7.6 meq O₂/g, and saponification value 382.1 mg KOH/g. A 2³ factorial experimental design was applied with three factors: methanol/oil molar ratio (6:1 and 9:1), reaction time (60 and 90 minutes), and catalyst concentration (1.0% and 2.0% w/w), performing three replicates per trial. The yields obtained ranged from 29.08% to 96.95%, with the optimal treatment being that with a 9:1 molar ratio, 90 minutes reaction time, and 1.0% catalyst concentration, which provided the highest yield of 96.95%. Statistical analysis by ANOVA showed that all three factors have significant effects on yield (p<0.05), with molar ratio and reaction time having the greatest influence. The biodiesel obtained presented properties within the parameters established by ASTM D6751 standard, with density between 0.802-0.902 g/ml, kinematic viscosity 4.97-5.92 mm²/s, and fatty acid methyl ester (FAME) content between 74.5-88.4%. It is concluded that waste cooking oil from Requena canteens constitutes a viable raw material for the production of acceptable quality biodiesel through alkaline transesterification.